Pregabalin and PR interval prolongation: any association? - Amin, Osama Shukir Muhammed (International Journal of Advances in Medicine, 2019)
Background: Pregabalin is a well-tolerated medication that is commonly used in the treatment of chronic pain, epilepsy, fibromyalgia, and generalized anxiety disorders. A variety of pregabalin-related cardiac side effects have been described in the literature and first-degree AV block is a well-known consequence. We aimed to investigate whether pregabalin prolongs the PR interval or not. Methods: This cross-sectional observational study was conducted at the Shorsh Military General Teaching Hospital, Iraq. A total of 80 patients, who had a multitude of cervical and lumbosacral radiculopathies were enrolled consecutively, from November 1, 2017, to January 31, 2019. Forty patients who were receiving pregabalin (the treatment group) were age-matched and gender-matched with another group of 40 patients who hadn’t been prescribed pregabalin (the control group). A single 12-lead ECG was done in all patients and the PR interval was calculated; a value of >0.20 second is considered a prolongation in the PR interval and defines first-degree AV block. Results: Thirteen patients (32%; 7 males and 6 females) demonstrated a prolongation in the PR interval in the pregabalin arm while the PR interval was prolonged in 5 patients only in the control group (12%; 2 males and 3 females). There was no statistical difference between the maximum PR prolongation in both groups (p-value=0.13; 95% CI, -0.0121 to 0.0317). Conclusions: This study hasn’t found a statistically significant prolongation in the PR interval among patients taking oral pregabalin monotherapy. Whether this observation is clinically significant or not, it needs further analytic studies to uncover its importance.